Development of 9 (Nine) maize hybrids with high yield potential and competitive agronomic characteristics for the highlands, mid-altitudes and lowlands of Mexico. - CGIAR Research Program on Maize (2020)
These hybrids can be scaled to public or private seed system units to carry out seed producibility research trials.